2022
DOI: 10.2478/jesm-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysing Work Performance of Lecturers in Southwestern Nigeria

Abstract: Lecturers in Nigerian universities, according to literature, are subjected to challenging workplace conditions that tends to inhibit their performance and subsequently, their ability to achieve the teaching, research and community development service functions of their job description. It, therefore, becomes pertinent that the work performance of lecturers be analysed to either support or negate existing literature on the subject matter. This study is qualitative in nature and data was gathered through in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The findings of this study indicated that more students engaged in actively participating in social media and praying for the strike to be over, relaxation, and learning of skills while gardening, getting a certification course or interim job were the least engaged by students during the ASUU strike. The findings corroborated the conclusions of Adisa and Oladejo, (2022);Okoli, Oguejiofor, and Okoli, (2019) and Amadi and Urho (2016) that students engaged in relaxation, praying and learn skills during the ASUU strike.…”
Section: Analysis Of Research Objectivessupporting
confidence: 87%
See 2 more Smart Citations
“…The findings of this study indicated that more students engaged in actively participating in social media and praying for the strike to be over, relaxation, and learning of skills while gardening, getting a certification course or interim job were the least engaged by students during the ASUU strike. The findings corroborated the conclusions of Adisa and Oladejo, (2022);Okoli, Oguejiofor, and Okoli, (2019) and Amadi and Urho (2016) that students engaged in relaxation, praying and learn skills during the ASUU strike.…”
Section: Analysis Of Research Objectivessupporting
confidence: 87%
“…During ASUU strike, lecturers refuse to work as they protest for poor conditions of or work. ASUU strike is now likened to other social vices such as: examination malpractice and corruption (Adisa & Oladejo, 2022). Like corruption, ASUU strike is considered as social problem which has eaten into the time of students, which in return had made it difficult for proper trained students within the specified time frame of study.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Work performance assesses whether a person does their work to the very best (Adisa & Oladejo, 2022). Positive performance is an essential principle for organisational accomplishment.…”
Section: Introductionmentioning
confidence: 99%
“…Many academic staff members in Nigerian universities must face some unpleasant workplace situations. They are thus less inclined to teach, do excellent research, and engage in community development initiatives (Adisa & Oladejo, 2022). A multitude of social vices, including cultism, malpractice, corruption, and hooliganism, as well as insufficient budget, subpar facilities, and unsuitable instructional aids (laboratories, projectors, libraries, and computers), plague public institutions.…”
Section: Introductionmentioning
confidence: 99%